High energy level diet improves the growth performance and rumen fermentation of yaks in cold weather - Zhu, Yanbin; Sun, Guangming; Luosang-dunzhu,; Li, Xin; Luosang-zhaxi,; Suolang-zhaxi,; Suolang,; Ciyang,; Cidan-yangji,; Basang-wangdui,; Pan, Feng; Peng, Quanhui (Frontiers in Veterinary Science, 2023)
This research investigated the effect of different dietary energy feed levels on the growth performance, immunity, rumen fermentation characteristics, and rumen methanogens of growing yak in the cold season. A total of 24 healthy yaks of 2 years old with similar body weight (141.7 ± 3.34kg) were randomly divided into three treatment groups according to a randomized complete block design. Three groups of yaks were fed with diets containing metabolizable energy 7.20, 7.89, 8.58 MJ/kg DM and named with low, medium, and high energy groups, respectively. Before the 56 days growth trial, the animals were given a 15-day acclimatization period to get familiar with enclosure and diet. The results showed that the average daily feed intake of the high-energy group was higher than the low-energy group (p = 0.006). Plasma aspartate aminotransferase (p = 0.004), alanine aminotransferase (p < 0.001), and interferon-γ (p < 0.001) in the high-energy group were lower than the low-energy group. In contrast, the superoxide dismutase (p < 0.001), immunoglobulin G (p < 0.001), and interleukin 2 (p = 0.002) were higher than the low energy group. The rumen microbial protein (p = 0.025), total volatile fatty acids (p = 0.029), and neutral detergent fiber digestibility (p = 0.050) in high energy group were higher than low energy group, whereas the acetate: propionate (p = 0.001) and ammonium nitrogen (p = 0.001) were lower than the low energy group. The plasma metabolomics results displayed that yak fed with a high-energy diet augmented the metabolism of arginine, proline, purine, taste transduction, pyrimidine, and glutathione pathways. The relative abundance of Methanobrevibacter in the high-energy group was lower (p < 0.001), whereas the relative abundance of Methanosphaera (p < 0.001) was higher than in the low-energy group. The results of the current study suggested that a high-energy diet in growing yaks during the cold season can improve growth performance, rumen microbial protein synthesis, antioxidants, and immunity.